A novel scoring system for the early detection of anastomotic leakage: bedside leak score—a pilot study - Ozata, Ibrahim H.; Bozkurt, Emre; Sucu, Serkan; Karahan, Salih N.; Camci, Furkan; Cetin, Feyza; Ozoran, Emre; Agcaoglu, Orhan; Balik, Emre; Bugra, Dursun (Frontiers in Surgery, 2023)
Background: Anastomotic leakage is a major complication in colorectal surgery resulting in significant morbidity & mortality. Despite significant progress in surgical technique, anastomotic leakage rates remain stable. Early diagnosis of anastomotic leak was proven to reduce adverse outcome and improve survival. Objective: This study aims to find a novel scoring system to detect anastomotic leak after colorectal surgery using inflammatory and nutritional indicators. Our purpose was to analyze the diagnostic accuracy of leak score (((CRP POD3))/((CRP POD1)*preoperative albumin level)) in predicting postoperative complications. Design Colorectal cancer patients, who underwent curative surgery in Koc University Hospital between 2014 and 2018 were included in the study. Patients were categorized into two groups depending on the presence of anastomotic leak and compared in terms of preoperative albumin levels, CRP levels in postoperative day 1 and day 3, anastomotic leak rates, length of hospital stay and CRP quotient which is calculated by dividing POD 3 CRP level to POD 1 CRP level. Bedside leak score is calculated dividing CRP quotient by preoperative albumin. Predictive value of bedside leak score, CRP quotient and preoperative albumin levels in estimating anastomotic leak was analyzed and a cut-off value for the leak score was calculated. Results A total of 183 patients were included in the study. Leak score, CRP POD 3 to 1 ratio and preoperative albumin levels were found to successfully detect anastomotic leakage. Area under the curve for the leak score was calculated as 0.78. Optimal cut-off value was found to be 50.3 for the Bedside Leak Score, which shows 90.9% sensitivity and a 59.3% specificity. Conclusion Leak score may represent a valuable diagnostic tool to detect patients at risk for anastomotic leakage after colorectal surgery and plan the better strategy to reduce morbidity, mortality and associated costs. However, further multicenter studies with large cohorts will be necessary to confirm these results.